Performance of Guinea Fowl Numida Meleagris Fed Varying Levels of Poultry Droppings - Adeyemo, A.I.; Oyejola, O. (International Journal of Poultry Science, 2004)
Six hundred guinea fowl pullets, 5 week old, were used for a 30 week feeding trial to test the replacement value of poultry droppings (PD) for blood meal, a conventional protein ingredient, in animal feed. Guinea fowl is a wild bird found in the savanna forests of West Africa. There were four dietary treatments namely, 0, 20, 40 and 60% PD replacement of blood meal. The birds were kept in deep litter houses for 20 weeks. Feed and water were offered ad libitum. At the 20th week, 10 birds were randomly selected from each of the four dietary treatments and starved for one day. They were killed in the slaughter house by cutting the neck through the jugular vein. This was used to determine the carcass parameters. The remaining birds were transferred into the layers house, where the following parameters were determined: body weight gain, feed intake, feed conversion, age at first lay, Percentage hen day production, egg weight, shell thickness and yolk colour. Results show that body weight gain and feed conversion decreased with the level of PD in the diet. There was no significant difference between the birds in carcass parameters in all the treatments except in oviduct length where its values decreased with the level of PD in the diet and significant differences (P<0.05) were observed among the birds raised on 0 and 60% PD. The birds on 0% PD attained point of lay two weeks earlier than those on 60% PD. And there was a significant difference (P<0.05) between the birds on 0% PD and those on 60% PD diets in age at first lay. However, there was no significant difference among birds raised on diets with PD below 60% PD. Feed intake increased with the level of PD and there was a significant difference (P0<0.05) between those raised on 0 and 60% PD diets. Mortality was very low as only two birds were recorded dead in the 60% PD diet throughout the experimental period. It was concluded that PD can be used to replace blood meal in the diet of guinea fowl up to 40% without any adverse effect on its performance.